2012
DOI: 10.1038/emboj.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

A novel miR-155/miR-143 cascade controls glycolysis by regulatinghexokinase 2in breast cancer cells

Abstract: Cancer cells preferentially metabolize glucose through aerobic glycolysis. This phenomenon, known as the Warburg effect, is an anomalous characteristic of glucose metabolism in cancer cells. Chronic inflammation is a key promoting factor of tumourigenesis. It remains, however, largely unexplored whether and how pro-tumourigenic inflammation regulates glucose metabolism in cancer cells. Here, we show that pro-inflammatory cytokines promote glycolysis in breast cancer cells, and that the inflammation-induced miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
284
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 321 publications
(302 citation statements)
references
References 58 publications
16
284
0
2
Order By: Relevance
“…23 A and B) after a 1-h TNF treatment. miR155 and miR146 have been shown to be induced by NFkB during inflammation (27,28), and miR155 has been shown to suppress miR143 (29).…”
Section: Coordinated and Complex Regulation Of The Transcriptome And Rnamentioning
confidence: 99%
“…23 A and B) after a 1-h TNF treatment. miR155 and miR146 have been shown to be induced by NFkB during inflammation (27,28), and miR155 has been shown to suppress miR143 (29).…”
Section: Coordinated and Complex Regulation Of The Transcriptome And Rnamentioning
confidence: 99%
“…Given our previous finding that IL-6 and miR-155 repress mir-143 via targeting its transcriptional activator C/EBPβ in MDA-MB-231 cells [6], which also occurred in MCF-7 cells ( Figure 1A and Supplementary information, Figure S3A), we hypothesized that targeting C/EBPβ might be responsible for the miR-155-mediated repression of the other 4 miRNAs. To test this hypothesis, we searched the human P mir-376a , P mir-198 , P mir-98 and P mir-205 and found that, similar to P mir-143 , these 4 promot- Figure 1 miR-155 regulates miRNA expression in breast cancer cells by targeting ETS-1 and C/EBPβ.…”
mentioning
confidence: 99%
“…miRNA-155 (miR-155) has been documented as one of the most prominent miRNAs linking inflammation to cancer [4]. On one hand, mir-155 is ubiquitously induced by inflammation stimuli [3]; on the other hand, miR-155 leads to the constitutive activation of pro-tumorigenic inflammatory STAT3 signaling by targeting socs1 [5] and conveys the inflammatory signals to the Warburg effect by upregulating hexokinase-2 [6]. We previously observed that pro-inflammatory cytokine interleukin-6 (IL-6)-induced miR-155 represses a specific miRNA gene mir-143 through targeting a transcription factor [6]; however, it is unclear how generally this mechanism might be utilized in the regulation of miRNAs by inflammation.…”
mentioning
confidence: 99%
See 2 more Smart Citations